2018
DOI: 10.1515/msp-2018-0026
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of preformed mixed nano-carbon structure from low rank coal

Abstract: Coal is a natural energy resource which is mainly used for energy production via combustion. Coal has nanocrystals embedded in it, formed during the coalification process, and is an ideal precursor for nano-carbon dots and diamonds. Herein, we report a facile top-down method to synthesise nanodots and diamonds of the size of 5 nm to 10 nm from three different types of coal by simple chemical leaching. TEM analysis revealed the formation of a mixture of carbon dots, graphene layers, and quantum dots in bitumino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The disappearance of these peaks in the XRD pattern for WTP‐t after demineralization indicated that the minerals in raw anthracite were effectively removed. After high temperature graphitization, the (002) peaks for G‐WTP and G‐WTP‐t become abnormally sharp because of the disappearance the γ peak (∼20) which is stand for of aliphatic carbon on the edge of aromatic lamellae . However, this peak became more symmetrical with the increase in rank because of the progressive removal of disordered carbon during leaching.…”
Section: Resultsmentioning
confidence: 99%
“…The disappearance of these peaks in the XRD pattern for WTP‐t after demineralization indicated that the minerals in raw anthracite were effectively removed. After high temperature graphitization, the (002) peaks for G‐WTP and G‐WTP‐t become abnormally sharp because of the disappearance the γ peak (∼20) which is stand for of aliphatic carbon on the edge of aromatic lamellae . However, this peak became more symmetrical with the increase in rank because of the progressive removal of disordered carbon during leaching.…”
Section: Resultsmentioning
confidence: 99%
“…The 1381 cm −1 peak is due to the presence of cyclic carbon groups. The band at 2922 cm −1 arises from the asymmetric vibration of sp 3 bond in CH 2 and CH 3 groups in the hydrocarbon network 11 14 . The peak at 2852 cm −1 is ascribed to the overlapping of symmetric vibration of the sp 3 band for CH 3 and CH 2 functional groups.…”
Section: Resultsmentioning
confidence: 99%
“…56−58 As the rank of coal falls, the dense carbon ring structure of coal-based GQDs loosens the hexagonal structure and the content of sp 2 carbons becomes less, producing a vacancy defect. 59,60 Low-grade (low-quality) coals are becoming increasingly important in light of the declining coal quality around the world. Kumar Thiyagarajan et al 49 synthesized CNs of diverse size and functionalities from low-grade coal lignite following different synthesis techniques, such as refluxing, microwave radiation, and laser ablation in ethylenediamine solution, named as CNP1, CNP2, and CD3, respectively.…”
Section: Synthesis and Structure Of Cns From Coalmentioning
confidence: 99%
“…The rank of coal is one of the crucial factors controlling the characteristics of the synthesized CNs. A coal structure study showed that low- and medium-ranked coal comprised more functional groups, side chains, bridge bonds, hydrogen bonds, and loose structures, with few layers and small aromatic rings. As the rank of coal falls, the dense carbon ring structure of coal-based GQDs loosens the hexagonal structure and the content of sp 2 carbons becomes less, producing a vacancy defect. , Low-grade (low-quality) coals are becoming increasingly important in light of the declining coal quality around the world.…”
Section: Synthesis and Structure Of Cns From Coalmentioning
confidence: 99%